Chilling injury in avocados and its prevention with thermal treatment - Donadon, J. R. [UNESP]; Durigan, J. F. [UNESP]; Morgado, C. M.A. [UNESP]; Durigan, M. F.B. [UNESP] (International Society for Horticultural Science (ISHS), 2012)
The combinations of temperature and time which can cause chilling injuries in avocados 'Geada', 'Quintal' and 'Fortuna' were determined. The binomial 4°C/28 days was selected to determine the activity of peroxidase (POD), polyphenoloxidase (PPO), polygalacturonase (PG) and methylesterase pectin (PME). The respiratory activity was also evaluated. The fruits were stored at this condition until being transferred to ambient conditions (22°C and 77% RH) until maturity, when they were compared to fruits stored permanently at this environment, after being cleaned (control). In the second part of this work, different hydrothermal treatments were tested to prevent or minimize chilling injuries. Avocados 'Geada', 'Quintal' and 'Fortuna' were treated at 38°C for 0, 30, 60 and 90 minutes before storage at 4°C for 28 days. It was observed that the activity of enzymes associated to browning, POD and PPO, and to maturation, PG and PME, had become greater in fruits stored at 4°C, or when they were transferred to environmental conditions. Fruits subjected to refrigeration, after transferred to environment, presented lower respiratory peak intensity and it occurred earlier than the others. Treatments using 38°C for 60 and 90 min minimized the symptoms of chilling injury in avocados 'Geada' while for 'Quintal' the most efficient was 38°C for 60 min. In 'Fortuna' these treatments did not minimize the damage by cold.
Keywords: Enzyme; Heat; Persea americana; Postharvest; Storage